1994
DOI: 10.1002/ijc.2910570218
|View full text |Cite
|
Sign up to set email alerts
|

The epstein‐barr virus latent membrane protein‐1 (LMP1) induces interleukin‐10 production in burkitt lymphoma lines

Abstract: Human interleukin-10 (h-IL-10) is a pleiotropic cytokine with stimulatory activity on B-lymphocytes. Recent evidence indicates that infection with Epstein-Barr virus (EBV) induces h-IL-10 production in B-cells and that this cytokine may contribute to EBV-induced B-cell transformation. It is not known whether h-IL-10 induction by EBV correlates with distinct phenotypic features of the infected cells or with the expression of particular viral genes. We have approached these questions by investigating the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
84
2
1

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(92 citation statements)
references
References 22 publications
5
84
2
1
Order By: Relevance
“…In B-lymphocytes, LMP1 is able to upregulate a number of cellular genes, including the apoptosisinhibiting bcl-2 gene (Henderson et al, 1991;Wang et al, 1996) as well as inducing IL-10, a potent inhibitor of T cell activation (Nakagomi et al, 1994). The transforming effects of LMP1 and its particularly high level expression in the HRS cells of EBV-associated HD indicate a role for this protein in the pathogenesis of EBV-positive HD and suggest important biological differences in HD that may be dependent upon EBV status (Oudejans et al, 1997).…”
mentioning
confidence: 99%
“…In B-lymphocytes, LMP1 is able to upregulate a number of cellular genes, including the apoptosisinhibiting bcl-2 gene (Henderson et al, 1991;Wang et al, 1996) as well as inducing IL-10, a potent inhibitor of T cell activation (Nakagomi et al, 1994). The transforming effects of LMP1 and its particularly high level expression in the HRS cells of EBV-associated HD indicate a role for this protein in the pathogenesis of EBV-positive HD and suggest important biological differences in HD that may be dependent upon EBV status (Oudejans et al, 1997).…”
mentioning
confidence: 99%
“…28,34 It has been shown also that LMP1 alone is able to induce IL-10 in BL cells but the signaling cascades involved are not known. 16 The precise mechanisms are not yet fully understood. However it has been described that LMP1 triggers NF B and JNK/AP1 activities but clear links of the activation of both signal cascades to the known EBV-activated cellular genes are so far missing.…”
Section: Discussionmentioning
confidence: 99%
“…2 It has been shown that in contrast to normal hematopoietic cells, in EBV-immortalized B cells, EBV-positive Burkitt's lymphoma (BL) cells and in CD40 stimulated B cells, IL-10 is expressed. 6,[13][14][15][16] However, the mechanism of the IL-10 induction in B cells is still unclear. 15,17,18 IL-10 induction by stimulation of human blood cultures with bacterial lipopolysaccharide (LPS) was found to be TNF and cAMP-dependent and shows large interindividual variations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations